Information Technology Governance Archetype in an Indonesian University - Riza Afriza Islami; I Made Sukarsa; I Ketut Adi Purnawan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Information Technology (IT) governance is used as a structure and control in alignment of IT functions and business goals. One of ABC University’s business goal is to achieve World Class University in 2021. This paper presents a study in one of IT governance’s component, likely structure of IT decisions right or archetype. It is needed to evaluate right applied archetype to achieve the alignment of business goals on five keys of IT decisions, namely IT principles, IT architecture, IT infrastructure, business application needs, and IT investment. COBIT 4.1 and the research of Weill and Ross (CISR) were used as the framework. The study was conducted by collecting data through observation, questionnaires, and interviews, as well as data analysis based on the existing conditions, and respondents’ perception.The analysis shows that there are still weaknesses in the existing IT governance conditions and archetype, so as it’s advisable the appropriate improvement recommendations.